Correlation between the Serum Level of Interleukin-2 in Hemodialysis Patients and Severity of Renal Pruritus - Radema Pranata; Yuli Kurniawati; Fitriani Fitriani; Legiran; Soenarto Kartowigno; Nopriyati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Renal pruritus (RP) is a condition or symptom that is often found in end-stage chronic kidney disease (CKD) undergoing hemodialysis (HD). The etiology of RP is multifactorial, one of it due to inflammation mediated by interleukin 2 (IL-2). Study on the correlation between serum level of IL-2 and the severity of RP is still limited. This study will analyze the correlation between serum level of IL-2 in patients undergoing HD and the severity of RP. Our method is cross sectional design at Hemodialysis Installation of Dr. Mohammad Hoesin Hospital. Serum level of IL-2 examined by ELISA, the severity of RP assessed by a 5 dimensional pruritus scale. Inclusion criteria in this study included HD patients with RP ≥ 9, age ≥ 18 years and willing to sign informed consent. The results from 28 male (59.6%) and 19 female (40.4%) are the mean serum level of IL-2 (pg/ml) is 0.424 ± 0.077. The mean RP severity score is 18.98 ± 2.74. A strong positive correlation between serum level of IL-2 and the severity of RP (r = 0.750, p = 0,000). Our conclusion is the increase of serum level IL-2 in line with severity of RP.